Metagenomic probing toward an atlas of the taxonomic and metabolic foundations of the global ocean genome - Laiolo, Elisa; Alam, Intikhab; Uludag, Mahmut; Jamil, Tahira; Agusti, Susana; Gojobori, Takashi; Acinas, Silvia G.; Gasol, Josep M.; Duarte, Carlos M. (Frontiers in Science, 2024)
The global ocean genome (the pool of genes in marine organisms and the functional information they encode) is a major, untapped resource for science and society with a growing range of biotechnology applications in sectors such as biomedicine, energy, and food. Shotgun sequencing and metagenomics can now be used to catalog the diversity of ocean microbial life and to explore its functional potential, but has been limited by sample coverage, access to suitable sequencing platforms, and computational capacity. Here we provide a novel synthesis of the global ocean genome based on analysis of 2,102 sampled ocean metagenomes, with gene assembly and annotation via the KAUST Metagenome Analysis Platform (KMAP) Global Ocean Gene Catalog 1.0 containing 308.6 million gene clusters. Taxonomically, we report the distribution of marine genes across the tree of life and different ocean basins and depth zone biomes. Functionally, we map its relationship to protein families and biogeochemical processes, including the major microbial metabolic pathways that process three elements that play fundamental roles in biogeochemical cycles and are relevant to climate change. These data extend our understanding of the complex, dynamic nature of the ocean microbiome and its metabolic capabilities. Further research is of critical global importance both to unlock the potential of the ocean genome and to understand and predict the effects of human-induced changes, including pollution and climate change. Further hypothesis-driven research should target under-sampled deep sea and benthic microbial communities using enhanced metagenomic methods, to better understand marine ecosystem functioning. Investment in the necessary computational capacity is essential, as are suitable intellectual property frameworks.